1985
DOI: 10.1111/j.1476-5381.1985.tb08832.x
|View full text |Cite
|
Sign up to set email alerts
|

Histamine is an antagonist of the acetylcholine receptor at the frog endplate

Abstract: The effects of histamine on the acetylcholine (ACh) receptor‐channel complex were examined by means of voltage‐clamp at the frog endplate. ACh was ionophoretically applied to the endplate. Histamine was added to the perfusate. Histamine (100 nM − 1 mM) reversibly depressed the peak amplitude of the ACh‐induced inward current in a dose‐dependent manner. The double reciprocal plot of the dose‐response relationship between the peak ACh current and the amount of ACh applied suggested that histamine (100 μM) depres… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

1986
1986
2000
2000

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(1 citation statement)
references
References 17 publications
0
1
0
Order By: Relevance
“…A fast depolarization of this preparation can be evoked by the activation of nicotinic, GABAA and 5-HT3 receptors, so we first considered whether histamine could be activating one of these receptors. It is known that histamine interacts with the nicotinic receptor at the neuromuscular junction, albeit in an apparently competitive antagonist manner (Ariyoshi et al, 1985), but we tested for the possibility that it could activate a nicotinic response on this preparation. The resistance of this response to mecamylamine and the small effect of (+ )-tubocurarine indicated that the opening of nicotinic receptor-linked ion channels was improbable.…”
Section: Discussionmentioning
confidence: 99%
“…A fast depolarization of this preparation can be evoked by the activation of nicotinic, GABAA and 5-HT3 receptors, so we first considered whether histamine could be activating one of these receptors. It is known that histamine interacts with the nicotinic receptor at the neuromuscular junction, albeit in an apparently competitive antagonist manner (Ariyoshi et al, 1985), but we tested for the possibility that it could activate a nicotinic response on this preparation. The resistance of this response to mecamylamine and the small effect of (+ )-tubocurarine indicated that the opening of nicotinic receptor-linked ion channels was improbable.…”
Section: Discussionmentioning
confidence: 99%